2009
DOI: 10.1213/ane.0b013e31819f1972
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ginkgo Biloba Extract EGb 761 on Mechanical and Cold Allodynia in a Rat Model of Neuropathic Pain

Abstract: We conclude that Ginkgo biloba extract, EGb 761, attenuates mechanical and cold allodynia in a rat model of neuropathic pain, and it may be useful for the management of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Moreover, none of the medications assessed in randomized controlled studies conducted has been found effective in Complex Regional Pain Syndrome i.e. CRPS (Kumar et al, 2007;Thomson & Jacques, 2009 (Comelli et al, 2008;Kanter, 2008;Kim et al, 2009;Muthuraman et al, 2008a;Wirth et al, 2005). Therefore, there is an ample scope of new medicine from plant origin to combat the neuropathic pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, none of the medications assessed in randomized controlled studies conducted has been found effective in Complex Regional Pain Syndrome i.e. CRPS (Kumar et al, 2007;Thomson & Jacques, 2009 (Comelli et al, 2008;Kanter, 2008;Kim et al, 2009;Muthuraman et al, 2008a;Wirth et al, 2005). Therefore, there is an ample scope of new medicine from plant origin to combat the neuropathic pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that Ginkgo biloba contains many pharmacologically active components like flavone glycosides (kaempferol, isorhamnetin, quercetin) and terpen lactones like ginkgolides A, B and C and bilobalide [34]. Quercetin is a powerful antioxidant and has been reported to decrease thermal hyperanalgaesia and cold allodynia in diabetic rats [13].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kim et al reported that EGb761 attenuated mechanical and cold allodynia in a rat model of neuropathic pain [4] and Taliyan et al reported that EGb761 attenuated streptozotocin (STZ)-induced neuropathic pain behaviors by inhibiting oxidative and nitrosative stress [17]; however, it is still not clear how EGb761 exerts an antiallodynic effect on neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Gingko flavones glycosides are free radical scavengers [2]. Accumulating evidences suggest EGb761 reduces capsaicin-induced hindpaw licking in rats [3], attenuates mechanical and cold allodynia in a rat model of neuropathic pain [4], and increases pain-free walking distance in patients with intermittent claudication [5]. These analgesic properties are suggested to be mediated through the inhibition of a range of proinflammatory mediators including nitric oxide (NO) [6], interleukin-1β [7] and tumor necrosis factor α (TNFα) [8].…”
Section: Introductionmentioning
confidence: 99%